Analysis of Phonological Errors in Reading Arabic Texts on Muthala'ah Material (Students Class II D Putra Marhalah Tsanawiyah TMI Al-Amien Prenduan Academic Year 2022-2023) - Izzat Amini; Fahmi Hasan (al-Afkar, Journal For Islamic Studies, 2024)
This study aims to analyze phonological errors in reading Arabic texts on muthala'ah material and the factors causing these phonological errors. This study uses a descriptive qualitative approach to describe phonological errors and the causes of these errors. The data in this study was obtained from interviews with teachers teaching muthala'ah material and class II D students, besides that researchers also made direct observations in the field. The results of this research are phoneme changes in the use of thin (light) sounds instead of thick (heavy) voiced letters such as the use of phonemes /د/ to replace phonemes /ض/, the use of phonemes /ا/ to replace phonemes /ع/, and the use of phonemes /س/ to replace phonemes /ش, exchange of phonemes that have adjacent articulations such as the use of phonemes /س/ to replace phonemes /ص/ and the use of phonemes /س/ to replace phonemes /ث/ and eliminate phonemes that function as letters Mad. Namely: phoneme ا / in reading Arabic text on repeat material. While the factors causing phonological errors include internal factors including the lack of vocabulary owned by students, the lack of habituation to read Arabic texts and differences in student backgrounds, and external factors include the system of adding new vocabulary that has new phoneme sounds and the lack of attention of teachers in learning guidance to the development of students or students.